2003
DOI: 10.1002/fut.10109
|View full text |Cite
|
Sign up to set email alerts
|

An empirical investigation of the GARCH option pricing model: Hedging performance

Abstract: In this article, we study the empirical performance of the GARCH option pricing model relative to the ad hoc Black-Scholes (BS) model of Dumas, Fleming, and Whaley. Specifically, we investigate the empirical performance of the option pricing model based on the exponential GARCH (EGARCH) process of Nelson. Using S&P 500 options data, we find that the EGARCH model performs better than the ad hoc BS model both in terms of in-sample valuation and out-of-sample forecasting. However, the superiority of out-of-sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 25 publications
(77 reference statements)
2
10
0
Order By: Relevance
“…3;2016 value-at-Risk for an options portfolio was found to be unsatisfactory. Yung and Zhang (2003) compared the empirical performance of the ad hoc Black-Scholes model of Dumas, Fleming and Whaley with that of the EGARCH option pricing model and found that although the pricing performance of the EGARCH model was better this superior performance was small and insignificant. Also the hedging performance of the EGARCH model was found to be worse than that of the simpler ad hoc Black-Scholes model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…3;2016 value-at-Risk for an options portfolio was found to be unsatisfactory. Yung and Zhang (2003) compared the empirical performance of the ad hoc Black-Scholes model of Dumas, Fleming and Whaley with that of the EGARCH option pricing model and found that although the pricing performance of the EGARCH model was better this superior performance was small and insignificant. Also the hedging performance of the EGARCH model was found to be worse than that of the simpler ad hoc Black-Scholes model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, this best fitted asset model is not necessarily the optimal option pricing model minimizing the mean square error between the model option prices and the market values. To obtain the optimal option pricing model the implied GARCH model is introduced by matching the GARCH option prices with the market plain vanilla values (Fofana andBrorsen 2001, Yung andZhang 2003). This approach is analogous to the implied volatility function model in the Black-Scholes framework (Dupire 1994, Andersen andBrotherton-Ratcliffe 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Others such as Nelson (1991) and Bollerslev and Mikkelsen (1996) contributed significantly to the GARCH models. Heston and Nandi (2000), Yung and Zhang (2003) and Barone-Adesi et al (2008) are among the few empirical studies that adopted GARCH models in the option pricing model. There is a large amount of literature on GARCH models that aims to measure volatility, but the models cannot be reviewed as a variant of the BSM model, given that it is a firmly discrete-time theory.…”
Section: Realised Volatilitymentioning
confidence: 99%
“…We noted that there are studies that consider the midpoint of bid-ask quotes in order to reduce non-synchronous problems, such as Heston and Nandi (2000), Yung and Zhang (2003), Li and Pearson (2007) and Barone-Adesi et al (2008). Midpoints are based on bid and ask quotes, which are more frequently refreshed than trade prices.…”
Section: Data Sampling Proceduresmentioning
confidence: 99%